Reply to “Comment on ‘Conditionally exactly soluble class of potentials’ ” - de Souza Dutra, A. [UNESP] (American Physical Society (APS), 2000)
We show that the problems raised by Znojil [Phys. Rev. A ▪, ▪ (2000)] preceding paper, can be resolved and that, in fact, there exist the proposed singular conditionally, exactly solvable potentials [Phys. Rev. A 47, R2435 (1993)]. © 2000 The American Physical Society.